Polarizing plate and method for manufacturing same
By setting up a adjacent layer with high sulfur concentration on the thin polarizing film and combining with a polyvinyl alcohol-based resin film with high iodine concentration, the durability problem of the thin polarizing film in high temperature and high humidity environment is solved, and high transmittance and durability are achieved. Take into account both.
Patent Information
- Application Number
- CN202411133543.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-25
- Filing Date
- 2020-06-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing thin polarizing film has insufficient durability in high temperature and high humidity environments, making it difficult to take into account both high monolithic transmittance and durability.
A polarizing film composed of a polyvinyl alcohol-based resin film containing iodine, and an adjacent layer containing sulfur is provided on at least one side thereof, with a sulfur concentration of 0.5% by weight and an iodine concentration of 3% by weight and is provided by sulfuric acid. Polarized plate.
High durability and high single-chip transmittance in high temperature and high humidity environments are achieved, and the humidification durability of the thin polarizing film is significantly improved.
Smart Images

Figure CN119126289A_ABST
Abstract
Description
[0001] This case is a divisional application of an application with an application date of June 15, 2020, application number 202080046260.6, and invention name “Polarizing plate and method for manufacturing the polarizing plate”. Technical Field
[0002] The present invention relates to a polarizing plate and a method for manufacturing the polarizing plate. Background Art
[0003] In a liquid crystal display device, which is a representative image display device, polarizing films are arranged on both sides of the liquid crystal unit due to its image forming method. As a method for manufacturing a polarizing film, for example, the following method is proposed: a laminate having a resin substrate and a polyvinyl alcohol-based resin layer is stretched, and then dyed to obtain a polarizing film on the resin substrate (for example, Patent Document 1). According to this method, a polarizing film with a thinner thickness can be obtained, and therefore, it has attracted attention because it contributes to the thinning of image display devices in recent years. However, for thin polarizing films, further improvement of durability in high temperature and high humidity environments is sought.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-343521 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polarizing plate having high single-piece transmittance and excellent durability in a high-temperature and high-humidity environment, and a method for producing such a polarizing plate.
[0009] Solutions for solving problems
[0010] According to one aspect of the present invention, there is provided a polarizing plate including: a polarizing film composed of a polyvinyl alcohol-based resin film containing iodine; and an adjacent layer containing sulfur provided on at least one surface of the polarizing film.
[0011] In one embodiment, the adjacent layer further includes a polyvinyl alcohol-based resin.
[0012] In one embodiment, the sulfur concentration in the adjacent layer is 0.5 wt % or more.
[0013] In one embodiment, the sulfur is derived from sulfuric acid.
[0014] In one embodiment, the polarizing film has a thickness of 8 μm or less.
[0015] In one embodiment, the iodine concentration in the polarizing film is 3% by weight or more.
[0016] According to another embodiment of the present invention, a manufacturing method is provided, which is a manufacturing method of the above-mentioned polarizing plate, comprising: applying a polyvinyl alcohol-based resin aqueous solution containing sulfuric acid to at least one surface of a polarizing film to form an adjacent layer, wherein the pH of the polyvinyl alcohol-based resin aqueous solution containing sulfuric acid is below 2.5.
[0017] Effects of the Invention
[0018] According to the present invention, a polarizing plate having high single-piece transmittance and excellent durability in a high-temperature and high-humidity environment can be obtained. Such a polarizing plate can be obtained by providing a layer containing sulfur adjacent to a polarizing film. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.
[0020] Figure 2 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.
[0021] Figure 3 This is a schematic diagram showing an example of a drying and shrinking process using a heating roller.
[0022] Description of Reference Numerals
[0023] 10 polarizing plates
[0024] 12 polarizing film
[0025] 14 Adjacent layer
[0026] 16First protective layer
[0027] 18 Second protection layer DETAILED DESCRIPTION
[0028] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0029] A.Polarizing plate
[0030] The polarizing plate described in the embodiment of the present invention has: a polarizing film composed of a polyvinyl alcohol-based resin film containing iodine, and an adjacent layer containing sulfur provided on at least one surface of the polarizing film. The polarizing plate may further have a protective layer as needed. In the embodiment of the present invention, the sulfur contained in the adjacent layer is preferably derived from sulfuric acid, and the sulfur concentration in the adjacent layer is preferably 0.5 weight % or more. By providing such a layer adjacent to the polarizing film, the durability of the polarizing film in a high temperature and high humidity environment can be improved, and representatively, the ΔP described later can be within a specified range. The effect of the adjacent layer may be significant in a thin polarizing film. Compared with a thick polarizing film, a thin polarizing film has a high iodine concentration, an insufficient stability of iodine, and a humidification durability that easily becomes insufficient, but by providing the above-mentioned adjacent layer, the humidification durability can be significantly improved.
[0031] Figure 1 Schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. Polarizing plate 10a includes polarizing film 12 and adjacent layer 14 provided adjacent to one surface of polarizing film 12. Unlike the example shown in the figure, adjacent layers may be provided on both surfaces of the polarizing film.
[0032] Figure 2 It is a schematic cross-sectional view of a polarizing plate described in another embodiment of the present invention. The polarizing plate 10b has: a polarizing film 12, an adjacent layer 14 arranged adjacent to one surface of the polarizing film 12, a first protective layer 16 arranged on the side of the polarizing film 12 opposite to the side on which the adjacent layer 14 is arranged, and a second protective layer 18 arranged on the side of the adjacent layer 14 opposite to the side on which the polarizing film 12 is arranged. One of the first protective layer 16 and the second protective layer 18 can be omitted. In the case where the adjacent layer is provided only on one surface of the polarizing film, representatively, the protective layer on the adjacent layer side (the second protective layer 18 in the example shown in the figure) can be omitted. It should be noted that one of the first protective layer and the second protective layer can be a resin substrate for manufacturing the polarizing plate described in item B.
[0033] A-1.Polarizing film
[0034] As mentioned above, the polarizing film is composed of a polyvinyl alcohol (PVA) resin film containing iodine. The PVA resin constituting the PVA resin film (substantially a polarizing film) preferably includes a PVA resin modified by acetoacetyl. If it is such a structure, a polarizing film with a desired mechanical strength can be obtained. When the PVA resin as a whole is set to 100% by weight, the blending amount of the PVA resin modified by acetoacetyl is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight. If the blending amount is such a range, a polarizing film with more excellent mechanical strength can be obtained.
[0035] The thickness of the polarizing film is preferably 8 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, and particularly preferably 3 μm or less. The lower limit of the thickness of the polarizing film may be 1 μm in one embodiment and 2 μm in another embodiment. As described later, such a thickness can be achieved by, for example, making a polarizing film using a laminate of a thermoplastic resin substrate and a PVA-based resin layer coated on the thermoplastic resin substrate. When the polarizing film is made of a single PVA-based resin film, the thickness of the polarizing film may be, for example, 12 μm to 35 μm.
[0036] The iodine concentration in the polarizing film is preferably 3% by weight or more, more preferably 4% by weight to 10% by weight, and further preferably 4% by weight to 8% by weight. It should be noted that in this specification, "iodine concentration" refers to the amount of all iodine contained in the polarizing film. More specifically, in the polarizing film, iodine is present in an amount of I - ,I 2 ,I 3 - 、PVA / I 3 - Complex, PVA / I 5 - The iodine concentration in this specification refers to the concentration of iodine in all forms including complexes, etc. The iodine concentration is calculated, for example, from the intensity of fluorescent X-rays by fluorescent X-ray analysis and the thickness of the film (polarizing film).
[0037] The single-piece transmittance of the polarizing film is preferably 42.0% or more, more preferably 43.0% or more, and further preferably 44.0% or more. On the other hand, the single-piece transmittance is preferably 47.0% or less, and more preferably 45.0% or less. The durability of a thin polarizing film with a high single-piece transmittance in a high temperature and high humidity environment is sometimes reduced, but according to an embodiment of the present invention, even when a thin polarizing film has such a high single-piece transmittance, excellent durability in a high temperature and high humidity environment can be achieved. It should be noted that in this specification, when referred to as single-piece transmittance, orthogonal transmittance and polarization, it refers to the single-piece transmittance, orthogonal transmittance and polarization before the durability test. The polarization of the polarizing film is preferably 99.85% or more, more preferably 99.90% or more, and further preferably 99.95% or more. On the other hand, the polarization is preferably 99.998% or less. According to an embodiment of the present invention, it is possible to balance high single-piece transmittance and high polarization degree, and it is possible to achieve excellent durability in a high temperature and high humidity environment as described later. Typically, the single-piece transmittance is a Y value obtained by measuring using an ultraviolet-visible spectrophotometer and correcting for visibility. In addition, the single-piece transmittance is a value when the refractive index of one surface of the polarizing plate is converted to 1.50 and the refractive index of the other surface is converted to 1.53. Typically, the polarization degree is calculated as follows: Based on the parallel transmittance Tp and the orthogonal transmittance Tc measured using an ultraviolet-visible spectrophotometer and corrected for visibility, the following formula is used to calculate.
[0038] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0039] In one embodiment, representatively, the transmittance (single-sheet transmittance) of a thin polarizing film of less than 8 μm is measured as follows: a laminate of a polarizing film (surface refractive index: 1.53) and a protective layer (protective film) (refractive index: 1.50) is used as a measurement object and measured using an ultraviolet-visible spectrophotometer. Depending on the surface refractive index of the polarizing film and / or the refractive index of the surface of the protective layer in contact with the air interface, the reflectivity at the interface of each layer changes, and as a result, the measured value of the transmittance sometimes changes. Therefore, for example, when a protective layer having a refractive index other than 1.50 is used, the measured value of the transmittance can be corrected according to the refractive index of the surface of the protective layer in contact with the air interface. Specifically, the correction value C of the transmittance uses the reflectivity R of polarized light parallel to the transmission axis at the interface between the protective layer and the air layer. 1 (Transmission axis reflectivity) is expressed by the following formula.
[0040] C=R 1 -R 0
[0041] R 0=((1.50-1) 2 / (1.50+1) 2 )×(T 1 / 100)
[0042] R 1 =((n 1 -1) 2 / (n 1 +1) 2 )×(T 1 / 100)
[0043] Here, R 0 is the transmission axis reflectivity when using a protective layer with a refractive index of 1.50, n 1 is the refractive index of the protective layer used, T 1 is the transmittance of the polarizing film. For example, when a substrate (cycloolefin film, film with hard coating, etc.) with a surface refractive index of 1.53 is used as a protective layer, the correction amount C becomes about 0.2%. At this time, 0.2% is added to the transmittance obtained by the measurement, so that the polarizing film with a surface refractive index of 1.53 can be converted into the transmittance when using a protective layer with a refractive index of 1.50. It should be noted that according to the calculation based on the above formula, the transmittance T of the polarizing film is 1 The change in correction value C when changing 2% is 0.03% or less, and the transmittance of the polarizing film has a limited influence on the correction value C. When the protective layer has absorption other than surface reflection, appropriate correction can be performed according to the absorption amount.
[0044] In one embodiment, the change in polarization degree ΔP of the polarizing film after a 240-hour durability test at 60°C and 95% relative humidity may be -0.05% or more, preferably -0.03% or more, and more preferably -0.01% or more. The change in polarization degree ΔP is represented by the following formula.
[0045] ΔP=P 240 -P 0
[0046] (Where P 240 is the polarization degree after the durability test, P 0 The polarization degree before the durability test (the polarization degree described above)
[0047] The polarizing film can be made using a single PVA-based resin film, or can be made using a laminate of two or more layers including a PVA-based resin layer. As a specific example of a polarizing film obtained using a laminate, a polarizing film obtained using a laminate of a thermoplastic resin substrate and a PVA-based resin layer formed by coating the thermoplastic resin substrate can be cited. Details of the method for making such a polarizing film will be described later in item B.
[0048] A-2. Adjacent layer
[0049] The adjacent layer contains sulfur, and typically also contains a base resin for forming the layer. In the adjacent layer, sulfur may be contained in the form of a sulfur-containing compound, or in the form of ions derived from the sulfur-containing compound, or both.
[0050] The sulfur concentration in the adjacent layer is preferably 0.5 wt % or more, more preferably 0.8 wt % to 10.0 wt %, and further preferably 1.2 wt % to 8.0 wt %. If the sulfur concentration is within this range, a polarizing film having excellent durability in a high temperature and high humidity environment can be suitably obtained. The sulfur concentration in the adjacent layer can be calculated, for example, from the intensity of fluorescent X-rays obtained by fluorescent X-ray analysis and the thickness of the adjacent layer.
[0051] The sulfur contained in the adjacent layer is preferably derived from a compound containing sulfuric acid other than an alkali metal salt or an alkaline earth metal salt. Specifically, the content (total content) of alkali metals and alkaline earth metals in the adjacent layer is typically 0.1 wt % or less, preferably 0.05 wt % or less.
[0052] As the sulfur-containing compound of the sulfur source contained in the adjacent layer, sulfuric acid, peroxymonosulfuric acid, peroxydisulfuric acid and other sulfur-containing acids (preferably strong acids with pKa < 0) can be preferably exemplified. Among them, sulfuric acid can be preferably used. It is believed that by providing such an acid-containing layer adjacent to the polarizing film, protons (H + Therefore, by mixing the acid containing sulfur so that the sulfur concentration in the adjacent layer is within the above-mentioned suitable range, the effect of the present invention can be suitably obtained.
[0053] As the above-mentioned base resin, water-soluble resins such as PVA resins and acrylic resins can be listed. Among them, PVA resins can be preferably used. PVA resins are excellent in adhesion to polarizing films, and then, it is easy to form an aqueous solution with excellent operability, and it is possible to give appropriate mechanical strength to the resulting adjacent layer. As PVA resins, any and appropriate PVA resins can be used. As PVA resins, for example, the resins described later in item B-1-1 for the method for manufacturing polarizing plates can be listed.
[0054] The thickness of the adjacent layer is preferably set to 0.1 μm or more, more preferably set to 0.3 μm or more, and further preferably set to 0.5 μm or more. If the adjacent layer is too thin, the durability improvement effect in a high temperature and high humidity environment may become insufficient. On the other hand, the thickness of the adjacent layer can be set to 3 μm or less.
[0055] A-3. Protective layer
[0056] The first protective layer and the second protective layer are formed by any and appropriate films that can be used as protective layers of polarizing films. As specific examples of materials that become the main components of the film, cellulose resins such as triacetyl cellulose (TAC) can be listed; transparent resins such as polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth) acrylic acid, acetate, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic acid, urethane, (meth) acrylic acid urethane, epoxy, silicone, etc. can also be listed. In addition, glassy polymers such as siloxane polymers can also be listed. In addition, polymer films recorded in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, and for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0057] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (outer protective layer) disposed on the opposite side of the display panel is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. It should be noted that when the surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.
[0058] When the polarizing plate is applied to an image display device, the thickness of the protective layer (inner protective layer) configured on the display panel side is preferably 5μm to 200μm, more preferably 10μm to 100μm, and further preferably 10μm to 60μm. In one embodiment, the inner protective layer is a phase difference layer having an arbitrary and appropriate phase difference value. At this time, the in-plane phase difference Re (550) of the phase difference layer is, for example, 110nm to 150nm. "Re (550)" is the in-plane phase difference measured using light of a wavelength of 550nm at 23°C, and is calculated using the formula Re = (nx-ny) × d. Here, "nx" is the refractive index in the direction (i.e., the slow axis direction) when the in-plane refractive index reaches the maximum, "ny" is the refractive index in the direction orthogonal to the slow axis (i.e., the fast axis direction) in the plane, "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (film).
[0059] B. Manufacturing method of polarizing plate
[0060] The method for manufacturing a polarizing plate according to an embodiment of the present invention comprises: applying a PVA-based resin aqueous solution containing sulfuric acid to at least one surface of a polarizing film to form an adjacent layer, wherein the pH of the PVA-based resin aqueous solution is preferably below 2.5. According to the method for manufacturing a polarizing plate according to this embodiment, the polarizing plate described in item A can be suitably obtained.
[0061] B-1. Method for producing a polarizing plate using a laminate
[0062] The manufacturing method of the polarizing plate described in one embodiment of the present invention includes: forming a PVA-based resin layer on one side of a long thermoplastic resin substrate to form a laminate; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizing film; and applying a PVA-based resin aqueous solution containing sulfuric acid to at least one surface of the polarizing film to form an adjacent layer. By applying the above-mentioned PVA-based resin aqueous solution to form an adjacent layer containing sulfur, a polarizing plate with excellent durability in a high temperature and high humidity environment can be achieved. Preferably, the PVA-based resin layer is made into a polarizing film by sequentially performing an air auxiliary stretching treatment, a dyeing treatment, and an underwater stretching treatment on the laminate. The manufacturing method may also include performing the following drying and shrinking treatment: the laminate after the underwater stretching treatment is heated while being transported along the length direction, so that it shrinks by more than 2% in the width direction. At this time, the application of the PVA-based resin aqueous solution containing sulfuric acid can be performed after the underwater stretching treatment and before the drying and shrinking treatment, or after the drying and shrinking treatment.
[0063] B-1-1. Preparation of laminate
[0064] As a method for preparing a laminate of a thermoplastic resin substrate and a PVA-based resin layer, any appropriate method may be adopted. Preferably, a coating liquid containing a PVA-based resin is applied to the surface of the thermoplastic resin substrate and dried to form the PVA-based resin layer on the thermoplastic resin substrate.
[0065] Any appropriate method may be used for applying the coating liquid, such as roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.). The coating / drying temperature of the coating liquid is preferably 50° C. or higher.
[0066] The thickness of the PVA-based resin layer is preferably 3 μm to 40 μm, more preferably 3 μm to 20 μm.
[0067] Before forming the PVA based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment) or an easy-adhesive layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA based resin layer can be improved.
[0068] As the thermoplastic resin substrate, any and appropriate thermoplastic resin film can be used. The details of the thermoplastic resin substrate are recorded in, for example, Japanese Patent Publication No. 2012-73580. The entire record of the publication is cited in this specification as a reference. Preferably, a polyester resin is used, and more preferably, a polyethylene terephthalate resin is used.
[0069] The coating liquid contains a PVA-based resin. Typically, the coating liquid is a solution obtained by dissolving a PVA-based resin in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, the solvent is preferably water.
[0070] As the above-mentioned PVA-based resin, any and appropriate resin can be used. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be listed. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be obtained according to JIS K 6726-1994. By using a PVA-based resin with such a saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, gelation is likely to occur.
[0071] The average degree of polymerization of the PVA-based resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined according to JIS K 6726-1994.
[0072] The PVA resin preferably includes an acetoacetyl-modified PVA resin. If this is the structure, a polarizing film with desired mechanical strength can be obtained. When the PVA resin as a whole is set to 100 wt %, the blending amount of the acetoacetyl-modified PVA resin is preferably 5 wt % to 20 wt %, and more preferably 8 wt % to 12 wt %. If the blending amount is in this range, a polarizing film with more excellent mechanical strength can be obtained.
[0073] The concentration of the PVA-based resin in the coating liquid is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is closely attached to the thermoplastic resin substrate can be formed.
[0074] The coating liquid preferably further contains a halide. As the halide, any and appropriate halide can be used. Examples thereof include iodide and sodium chloride. As the iodide, examples thereof include potassium iodide, sodium iodide and lithium iodide. Among these, potassium iodide is preferred.
[0075] The amount of the halide in the coating liquid is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA resin. If the amount of the halide exceeds 20 parts by weight, the halide may ooze out, and the polarizing film finally obtained may become turbid.
[0076] Generally speaking, the orientation of the polyvinyl alcohol molecules in the PVA resin increases due to the stretching of the PVA resin layer, but when the stretched PVA resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules is sometimes disordered and the orientation decreases. In particular, when a laminate of a thermoplastic resin substrate and a PVA resin layer is stretched in boric acid water, the orientation tends to decrease significantly when the laminate is stretched in boric acid water at a higher temperature in order to stabilize the stretching of the thermoplastic resin substrate. For example, the stretching of a PVA film alone in boric acid water is usually carried out at 60°C. In contrast, the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA resin layer is carried out at a high temperature of about 70°C. At this time, the orientation of the PVA at the initial stage of stretching may decrease before it rises due to the stretching in water. In contrast, by preparing a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate, and stretching the laminate at a high temperature in air (auxiliary stretching) before stretching the laminate in boric acid water, the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizing film obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved.
[0077] Additives may be further compounded into the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyols such as ethylene glycol and glycerol. Examples of surfactants include nonionic surfactants. These may be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.
[0078] B-1-2. Aerial auxiliary stretching treatment
[0079] In particular, in order to obtain high optical properties, a two-stage stretching method combining dry stretching (auxiliary stretching) and underwater stretching (preferably boric acid underwater stretching) can be selected. By introducing auxiliary stretching as in two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate, and it is possible to solve the problem of reduced stretchability due to excessive crystallization of the thermoplastic resin substrate in subsequent underwater stretching (preferably boric acid underwater stretching), and the laminate can be stretched to a higher ratio. Furthermore, when applying PVA-based resin on a thermoplastic resin substrate, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, it is necessary to reduce the coating temperature compared to the usual case of applying PVA-based resin on a metal roller, and as a result, the crystallization of the PVA-based resin may be relatively low and the problem of being unable to obtain sufficient optical properties may occur. In contrast, by introducing auxiliary stretching, even when applying PVA-based resin on a thermoplastic resin substrate, the crystallinity of the PVA-based resin can be improved, and high optical properties can be achieved. Furthermore, by simultaneously improving the orientation of the PVA-based resin in advance, it is possible to prevent problems such as a decrease in orientation and dissolution of the PVA-based resin when immersed in water in the subsequent dyeing step and stretching step, thereby achieving high optical properties.
[0080] The stretching method of aerial auxiliary stretching can be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rollers with different circumferential speeds). In order to obtain high optical properties, free-end stretching can be actively adopted. In one embodiment, the aerial stretching process includes a heating roller stretching process in which the above-mentioned laminate is stretched while being transported along its length direction using the circumferential speed difference between the heating rollers. Representatively, the aerial stretching process includes a regional stretching process and a heating roller stretching process. It should be noted that the order of the regional stretching process and the heating roller stretching process is not limited. The regional stretching process can be performed first, or the heating roller stretching process can be performed first. The regional stretching process can also be omitted. In one embodiment, the regional stretching process and the heating roller stretching process are performed in sequence. In addition, in other embodiments, in the tenter stretching machine, stretching is performed by holding the end of the film and widening the distance between the tenters along the flow direction (the expansion of the distance between the tenters becomes the stretching ratio). At this time, the distance of the tenters in the width direction (the direction perpendicular to the flow direction) is set in an arbitrarily close manner. It is preferable to set the stretch ratio in the flow direction in a manner closer to free-end stretching. In the case of free-end stretching, the shrinkage ratio in the width direction = (1 / stretch ratio) 1 / 2 to calculate.
[0081] The auxiliary stretching in the air can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio is the product of the stretching ratios of each stage. The stretching direction in the auxiliary stretching in the air is preferably substantially the same as the stretching direction in the underwater stretching.
[0082] The stretching ratio in the air auxiliary stretching is preferably 2.0 to 3.5 times. The maximum stretching ratio when the air auxiliary stretching is combined with the underwater stretching is preferably 5.0 times or more, more preferably 5.5 times or more, and further preferably 6.0 times or more relative to the original length of the laminate. In this specification, the "maximum stretching ratio" refers to the stretching ratio before the laminate is about to break, and refers to the stretching ratio at which the laminate is separately confirmed to break, and is 0.2 lower than its value.
[0083] The stretching temperature of the aerial auxiliary stretching can be set to any and appropriate value according to the forming material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate + 10 ° C, and particularly preferably above Tg + 15 ° C. On the other hand, the upper limit of the stretching temperature is preferably 170 ° C. By stretching at such a temperature, the crystallization of the PVA-based resin can be suppressed from proceeding rapidly, and the adverse conditions caused by the crystallization (for example, hindering the orientation of the PVA-based resin layer achieved by stretching) can be suppressed.
[0084] B-1-3. Insolubilization, dyeing and cross-linking
[0085] As needed, after the auxiliary stretching treatment in the air and before the stretching treatment in the water and the dyeing treatment, an insolubilization treatment is performed. Typically, the insolubilization treatment is performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Typically, the dyeing treatment is performed by dyeing the PVA-based resin layer with iodine. As needed, after the dyeing treatment and before the stretching treatment in the water, a crosslinking treatment is performed. Typically, the crosslinking treatment is performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described, for example, in Japanese Patent Gazette No. 2012-73580.
[0086] B-1-4. Underwater stretching
[0087] The underwater stretching treatment is performed by immersing the laminate in a stretching bath. According to the underwater stretching treatment, the laminate can be stretched at a temperature lower than the glass transition temperature (typically, about 80° C.) of the thermoplastic resin substrate and the PVA-based resin layer, and the PVA-based resin layer can be stretched to a high ratio while suppressing its crystallization. As a result, a polarizing film with excellent optical properties can be manufactured.
[0088] The stretching method of the laminate can be any and appropriate method. Specifically, it can be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing the laminate between rollers with different circumferential speeds). Preferably, free end stretching is selected. The stretching of the laminate can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio (maximum stretching ratio) of the laminate described later is the product of the stretching ratios of each stage.
[0089] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (boric acid underwater stretching). By using an aqueous solution of boric acid as a stretching bath, the PVA-based resin layer can be given rigidity and water resistance that can withstand the tension applied during stretching. Specifically, boric acid can generate tetrahydroxyborate anions in an aqueous solution and cross-link with the PVA-based resin by means of hydrogen bonds. As a result, the PVA-based resin layer can be given rigidity and water resistance, thereby being well stretched, and a polarizing film with excellent optical properties can be manufactured.
[0090] The above-mentioned boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight relative to 100 parts by weight of water, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher characteristics can be manufactured. It should be noted that an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent in addition to boric acid or a borate can also be used.
[0091] It is preferred to mix an iodide into the stretching bath (boric acid aqueous solution). By mixing an iodide, the dissolution of iodine adsorbed to the PVA-based resin layer can be suppressed. Specific examples of iodide are as described above. The concentration of iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight relative to 100 parts by weight of water.
[0092] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. If it is this temperature, it is possible to stretch to a high ratio while suppressing the dissolution of the PVA-based resin layer. Specifically, as described above, due to the relationship with the formation of the PVA-based resin layer, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably above 60°C. At this time, if the stretching temperature is lower than 40°C, considering the plasticization of the thermoplastic resin substrate caused by water, it may not be stretched well. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer becomes, and it may not be possible to obtain excellent optical properties. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0093] The stretching ratio based on the underwater stretching is preferably 1.5 times or more, more preferably 3.0 times or more. The total stretching ratio of the laminate is preferably 5.0 times or more, more preferably 5.5 times or more relative to the original length of the laminate. By achieving this high stretching ratio, a polarizing film with extremely excellent optical properties can be manufactured. This high stretching ratio can be achieved by adopting an underwater stretching method (boric acid underwater stretching).
[0094] B-1-5. Other treatments
[0095] It is preferred to perform a cleaning treatment after the stretching treatment in water and before the drying shrinkage treatment. Typically, the cleaning treatment is performed by immersing the PVA-based resin layer in an aqueous solution containing an iodide such as potassium iodide. The iodide concentration in the cleaning solution is preferably 0.5 wt % to 10 wt %, preferably 0.5 wt % to 5 wt %, and more preferably 1 wt % to 4 wt %. The temperature of the cleaning solution is generally 10° C. to 50° C., preferably 20° C. to 35° C. The immersion time is generally 1 second to 1 minute, preferably 10 seconds to 1 minute.
[0096] B-1-6. Drying shrinkage treatment
[0097] The above-mentioned drying shrinkage treatment can be carried out by the regional heating carried out by the heating area as a whole, or it can be carried out by heating the conveying roller (using the so-called heating roller) (heating roller drying method). It is preferred to use both of them. By using a heating roller to dry it, the heating warping of the laminate can be effectively suppressed, and a polarizing film with excellent appearance can be manufactured. Specifically, by drying the laminate along the state of the heating roller, the crystallization of the above-mentioned thermoplastic resin substrate can be effectively promoted to increase the crystallinity, even if the drying temperature is relatively low, the crystallinity of the thermoplastic resin substrate can be well increased. As a result, the rigidity of the thermoplastic resin substrate increases, and a state that can withstand the shrinkage of the PVA-based resin layer (polarizing film) caused by drying is presented, and warping can be suppressed. In addition, by using a heating roller, the laminate can be dried while maintaining a flat state, therefore, not only warping can be suppressed, but also the generation of wrinkles can be suppressed. At this time, the optical properties of the polarizing film can be improved by shrinking the laminate along the width direction using a drying shrinkage treatment. This is because the orientation of PVA and PVA / iodine complex can be effectively improved. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.
[0098] Figure 3Schematic diagram showing an example of drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by using the transport rollers R1 to R6 and the guide rollers G1 to G4 heated to a predetermined temperature. In the example shown in the figure, the transport rollers R1 to R6 are arranged in a manner that the surface of the PVA-based resin layer (polarizing film) and the surface of the thermoplastic resin substrate are alternately and continuously heated, but the transport rollers R1 to R6 may also be arranged in a manner that only one side of the laminate 200 (for example, the thermoplastic resin substrate surface) is continuously heated.
[0099] The drying conditions can be controlled by adjusting the heating temperature of the conveying roller (the temperature of the heating roller), the number of heating rollers, the contact time with the heating roller, etc. The temperature of the heating roller is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be increased well, the warping can be well controlled, and an optical laminate with extremely excellent durability can be manufactured. It should be noted that the temperature of the heating roller can be measured using a contact thermometer. In the example shown in the figure, 6 conveying rollers are provided, but there is no particular limitation as long as there are multiple conveying rollers. Conveying rollers are usually provided in 2 to 40 numbers, preferably 4 to 30 numbers. The contact time (total contact time) between the laminate and the heating roller is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and more preferably 1 to 10 seconds.
[0100] The heating roller can be set in a heating furnace (such as an oven) or in a normal production line (under room temperature environment). It is preferably set in a heating furnace equipped with an air supply unit. By combining the drying based on the heating roller and the hot air drying, the rapid temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of the hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10m / s to 30m / s. It should be noted that the wind speed is the wind speed in the heating furnace and can be measured by a mini blade type digital anemometer.
[0101] B-1-7. Formation of adjacent layer
[0102] The PVA-based resin aqueous solution containing sulfuric acid is applied to the polarizing film surface of the laminate (polarizing plate) of the thermoplastic resin substrate and polarizing film obtained by the above operation to form an adjacent layer. As a result, a laminate (polarizing plate) of a thermoplastic resin substrate / polarizing film / adjacent layer can be obtained. At this time, representatively, the thermoplastic resin substrate can be directly used as a protective layer of the polarizing film. In another embodiment, a resin film (forming a protective layer) is laminated to the polarizing film surface of the laminate of a thermoplastic resin substrate and a polarizing film, a laminate of a protective layer / polarizing film / thermoplastic resin substrate is made, and the thermoplastic resin substrate is peeled off from the laminate to make a laminate (polarizing plate) of a protective layer / polarizing film. The PVA-based resin aqueous solution containing sulfuric acid is applied to the polarizing film surface of the obtained polarizing plate. As a result, a laminate (polarizing plate) of a protective layer / polarizing film / adjacent layer can be obtained.
[0103] Typically, the PVA-based resin aqueous solution is an aqueous solution obtained by mixing sulfuric acid, a PVA-based resin, and water. The PVA-based resin is as described in the section B-1-1.
[0104] The concentration of the PVA resin in the above-mentioned PVA resin aqueous solution can be set in consideration of operability (applicability). The concentration can be adjusted in a manner such that the viscosity of the PVA resin aqueous solution becomes 1 mPa·sec to 300 mPa·sec. The concentration of the PVA resin in the PVA resin aqueous solution can be, for example, 0.1 wt % to 15 wt %, more preferably 0.5 wt % to 10 wt %.
[0105] The concentration of sulfuric acid in the aqueous PVA resin solution can be adjusted according to the desired sulfur concentration in the adjacent layer (in other words, the desired proton concentration (H + The pH of the PVA-based resin aqueous solution is preferably 2.5 or less, more preferably 2.3 or less, and further preferably 2.1 or less. The lower limit of the pH of the PVA-based resin aqueous solution is not particularly limited, but can be set to 0.5 or more in consideration of storage stability.
[0106] The adjacent layer can be formed by applying the above-mentioned PVA-based resin aqueous solution on the surface of the polarizing film and drying it as needed. As a coating method, any and appropriate method can be adopted. As a specific example, the method described in item B-1-1 as a coating method for forming a coating liquid for a PVA-based resin layer (polarizing film) can be cited. The drying temperature is, for example, 40°C to 100°C, and the drying time is, for example, 1 minute to 20 minutes.
[0107] B-2. Method for producing a polarizing plate using a single PVA-based resin film
[0108] In item B-1, a method for manufacturing a polarizing plate using a laminate of a thermoplastic resin substrate and a PVA-based resin layer coated on the thermoplastic resin substrate is described, but the present invention can also be applied to a method for manufacturing a polarizing plate using a single PVA-based resin film. Typically, this manufacturing method includes: stretching and dyeing a self-supporting PVA-based resin film to form a polarizing film; and coating an aqueous PVA-based resin solution containing sulfuric acid on at least one surface of the polarizing film to form an adjacent layer. More specifically, a long strip of PVA-based resin film is uniaxially stretched along the strip direction using a roll stretching machine while being swollen, dyed, cross-linked and cleaned to produce a polarizing film, and a PVA-based resin aqueous solution containing sulfuric acid is coated on the cleaned polarizing film. The coating of the PVA-based resin aqueous solution containing sulfuric acid can be carried out in the same manner as item B-1-7.
[0109] Example
[0110] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.
[0111] (1) Thickness
[0112] The polarizing plates of the examples and comparative examples were cut and the cross sections of the polarizing plates were observed using a scanning electron microscope (JSM7100F manufactured by JEOL Ltd.) to measure the thickness of the adjacent film. The thickness of the polarizing film was measured using an interference film thickness meter (MCPD-3000 manufactured by Otsuka Electronics Co., Ltd.).
[0113] (2) Single-element transmittance, orthogonal transmittance, and polarization
[0114] The single-piece transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured for the polarizing plates of the embodiments and comparative examples (for single-piece transmittance, for the laminate having the structure of protective layer / polarizing film) using an ultraviolet visible spectrophotometer (LPF200 manufactured by Otsuka Electronics Co., Ltd.) are set as Ts, Tp, and Tc of the polarizing film, respectively. These Ts, Tp, and Tc are Y values obtained by measuring and correcting the visibility using the 2-degree field of view (C light source) of JIS Z8701. The degree of polarization is calculated from the obtained Tp and Tc using the following formula.
[0115] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0116] Next, a glass (alkali-free glass) with alkali components removed was attached to the adjacent layer side of the polarizing plate with the aid of an adhesive, and the plate was placed in an oven set at a temperature of 60°C and a relative humidity of 95% for 240 hours for a durability test. The polarization degree P after the durability test was obtained by the same operation as above. 240 .
[0117] (3) Sulfur concentration in the adjacent layer (S concentration)
[0118] The sulfur concentration in the thin film (adjacent layer) was determined using a scanning fluorescent X-ray analyzer (ZSXPRIMUS IV, manufactured by Rigaku Corporation) according to the following procedure: First, a sample with a known thickness (μm) and sulfur concentration (wt%) (e.g., a sample with a certain amount of Na 2 SO 4 The fluorescence X-ray intensity (kcps) of the PVA resin film was used to prepare a standard curve. The standard curve of sulfur concentration in the film is expressed by the following formula:
[0119] (Sulfur concentration) = A x (fluorescent X-ray intensity) / (film thickness) - B
[0120] Here, A and B are constants that vary depending on the measuring device. For example, when ZSX PRIMUS IV (measurement sample diameter: 30 mm) is used as the measuring device, A is "0.0005" and B is "0.0005".
[0121] (4) Sodium concentration in the adjacent layer (Na concentration)
[0122] The sodium concentration in the film (adjacent layer) was determined using a scanning fluorescent X-ray analyzer (ZSXPRIMUS IV, manufactured by Rigaku Corporation) according to the following steps: First, the fluorescent X-ray intensity (kcps) of a sample with a known thickness (μm) and sodium concentration (wt%) (for example, a PVA-based resin film to which a certain amount of NaCl is added) was measured to prepare a calibration curve. The calibration curve of the sodium concentration in the film is expressed by the following formula:
[0123] (Sodium concentration) = A × (fluorescent X-ray intensity) / (film thickness) - B
[0124] Here, A and B are constants that vary depending on the measuring device. For example, when ZSX PRIMUS IV (measurement sample diameter: 30 mm) is used as the measuring device, A is "0.0054" and B is "0.0027".
[0125] [Example 1-1]
[0126] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0127] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin obtained by mixing polyvinyl alcohol (degree of polymerization: 4200, degree of saponification: 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting product was dissolved in water to prepare a PVA aqueous solution (coating liquid).
[0128] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0129] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).
[0130] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0131] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single-piece transmittance (Ts) of the polarizing plate finally obtained would be 44.0% (dyeing treatment).
[0132] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution obtained by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0133] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration of 4 wt %, potassium iodide concentration of 5 wt %) at a liquid temperature of 70°C, and was uniaxially stretched (underwater stretching treatment) along the longitudinal direction (length direction) between rollers with different circumferential speeds in such a manner that the total stretching ratio became 5.5 times.
[0134] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0135] Thereafter, the laminate was dried in an oven maintained at about 90° C. and brought into contact with a SUS heating roll maintained at a surface temperature of about 75° C. (drying shrinkage treatment). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 2%.
[0136] In this way, a polarizing film with a thickness of 5.0 μm was formed on the resin substrate, and a cycloolefin film (manufactured by ZEON, product name "G-Film") as a protective layer (protective film) was attached to the surface of the polarizing film using a UV curing adhesive (thickness of 1.0 μm). Thereafter, the resin substrate was peeled off to obtain a laminate having a protective layer / polarizing film structure. The single-piece transmittance (Ts) of the obtained laminate was 44.0%. Since the surface refractive index of the polarizing film / protective layer constituting the laminate was 1.53 / 1.53, the single-piece transmittance was a value obtained by correcting the actual measured value by +0.2% and converting it to a state of 1.53 / 1.50.
[0137] Next, a PVA-based resin aqueous solution (containing H 2 SO 4 PVA aqueous solution). 2 SO 4 The PVA aqueous solution contained 1.4 wt% sulfuric acid and 3.5 wt% polyvinyl alcohol (polymerization degree 2600, saponification degree 99.98 mol%), and the pH was 0.9. 2 SO 4 The coated film of the PVA aqueous solution was dried at 60° C. for 5 minutes to form an adjacent layer with a thickness of 0.4 μm, thereby obtaining a polarizing plate having a structure of protective layer / polarizing film / adjacent layer.
[0138] Table 1 shows ΔP, S concentration, and Na concentration in the adjacent layer of the obtained polarizing plate (substantially, a polarizing film).
[0139] [Example 1-2]
[0140] The H-containing film was applied so that the thickness of the adjacent layer would be 0.9 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0141] [Example 2-1]
[0142] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 1.0 (containing H 2 SO 4The sulfuric acid concentration in the PVA aqueous solution was 1.01 wt %), and a layer containing H was applied so that the thickness of the adjacent layer became 0.7 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0143] [Example 2-2]
[0144] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 1.2 (containing H 2 SO 4 The sulfuric acid concentration in the PVA aqueous solution was 0.58 wt%), and a layer containing H was applied so that the thickness of the adjacent layer became 0.7 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0145] [Example 2-3]
[0146] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 1.5 (containing H 2 SO 4 The sulfuric acid concentration in the PVA aqueous solution was 0.35 wt %), and a layer containing H was applied so that the thickness of the adjacent layer became 0.7 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0147] [Examples 2-4]
[0148] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 1.7 (containing H 2 SO 4 The sulfuric acid concentration in the PVA aqueous solution was 0.19 wt %), and a layer containing H was applied so that the thickness of the adjacent layer became 0.7 μm. 2 SO 4A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0149] [Example 2-5]
[0150] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 2.0 (containing H 2 SO 4 The sulfuric acid concentration in the PVA aqueous solution was 0.11 wt %), and a layer containing H was applied so that the thickness of the adjacent layer became 0.7 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0151] [Comparative Example 1]
[0152] Containing H 2 SO 4 The pH of the PVA aqueous solution was set to 2.6 (containing H 2 SO 4 The sulfuric acid concentration in the PVA aqueous solution was 0.04 wt%), and a layer containing H was applied so that the thickness of the adjacent layer became 1.2 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0153] [Comparative Example 2]
[0154] A sodium sulfate-containing solution containing 0.2 wt % of sodium sulfate and 3.5 wt % of polyvinyl alcohol (polymerization degree 2600, saponification degree 99.98 mol %) was used. 2 SO 4 The PVA aqueous solution (pH = 6.3) was used to replace the H 2 SO 4 The PVA aqueous solution was coated with Na in such a way that the thickness of the adjacent layer became 1.2 μm. 2 SO 4 A polarizing plate was prepared in the same manner as in Example 1-1 except that a PVA aqueous solution of 1.5% was used. Table 1 shows ΔP and the S concentration and Na concentration in the adjacent layer of the obtained polarizing plate (substantially a polarizing film).
[0155] [Reference example]
[0156] Uncoated with H 2 SO 4 The same operation as in Example 1-1 was performed except that the PVA aqueous solution was added (as a result, no adjacent layer was formed), and a polarizing plate (Ts: 44.0%) having a protective layer / polarizing film structure was obtained. The obtained polarizing plate (substantially a polarizing film) is shown in Table 1. It should be noted that the polarization degree P of the obtained polarizing plate (substantially a polarizing film) before the durability test was 0 The P of the polarizing plate of the embodiment and the comparative example having the adjacent layer is 99.90%. 0 Roughly the same value.
[0157] [Table 1]
[0158]
[0159] As is clear from Table 1, the polarizing plates of Examples of the present invention have excellent durability in a high-temperature and high-humidity environment.
[0160] Industrial Applicability
[0161] The polarizing plate of the present invention can be suitably used in a liquid crystal display device.
Claims
1. A polarizing plate, comprising: A polarizing film composed of a polyvinyl alcohol-based resin film containing iodine; and An adjacent layer containing sulfur disposed on at least one surface of the polarizing film, the adjacent layer does not include: a layer containing a crosslinking agent for a polyvinyl alcohol-based resin and a layer containing an oxazoline group-containing polymer, The sulfur is derived from sulfuric acid, The concentration of sulfur in the adjacent layer is 1.5 wt % or more, The adjacent layer further comprises a polyvinyl alcohol-based resin, The thickness of the adjacent layer is 0.3 μm or more.
2. The polarizing plate according to claim 1, wherein The sulfur concentration in the adjacent layer is 3.2 wt % or more.
3. The polarizing plate according to claim 1 or 2, wherein: The thickness of the adjacent layer is 3 μm or less.
4. The polarizing plate according to any one of claims 1 to 3, wherein The polarizing film has a thickness of 8 μm or less.
5. The polarizing plate according to any one of claims 1 to 4, wherein The iodine concentration in the polarizing film is 3 weight % or more.
6. The method for producing a polarizing plate according to any one of claims 1 to 5, comprising: A polyvinyl alcohol-based resin aqueous solution containing sulfuric acid is applied to at least one surface of the polarizing film to form an adjacent layer, wherein the polyvinyl alcohol-based resin aqueous solution does not include: a polyvinyl alcohol-based resin aqueous solution containing a cross-linking agent for the polyvinyl alcohol-based resin and a polyvinyl alcohol-based resin aqueous solution containing an oxazoline-containing polymer, The pH of the polyvinyl alcohol-based resin aqueous solution containing sulfuric acid is 2.0 or less, and the thickness of the adjacent layer is 0.3 μm or more.
Citation Information
Patent Citations
Highly durable polarizing plate, image display device using same, and method for producing polarizing plate
CN109154687A
High durable polarizing plate
JP2008070571A
Polarizing plate and optical member
US20030152718A1
Method for producing polarizer, polarizer, polarizing plate, optical film, and image display
WO2004113973A1
Curable composition, optical laminate, and image display device
WO2019116969A1
